Immunometabolism, Micronutrients, and Bariatric Surgery: The Use of Transcriptomics and Microbiota-Targeted Therapies - Shannon Galyean; Dhanashree Sawant; Andrew C. Shin (Mediators of Inflammation)
Background. Obesity is associated with the gut microbiota and decreased micronutrient status. Bariatric surgery is a recommended therapy for obesity. It can positively affect the composition of the gut bacteria but also disrupt absorption of nutrients. Low levels of micronutrients can affect metabolic processes, like glycolysis, TCA cycle, and oxidative phosphorylation, that are associated with the immune system also known as immunometabolism. Methods. MEDLINE, PUBMED, and Google Scholar were searched. Articles involving gut microbiome, micronutrient deficiency, gut-targeted therapies, transcriptome analysis, micronutrient supplementation, and bariatric surgery were included. Results. Studies show that micronutrients play a pivotal role in the intestinal immune system and regulating immunometabolism. Research demonstrates that gut-targeting therapies may improve the microbiome health for bariatric surgery populations. There is limited research that examines the role of micronutrients in modulating the gut microbiota among the bariatric surgery population. Conclusions. Investigations are needed to understand the influence that micronutrient deficiencies have on the gut, particularly immunometabolism. Nutritional transcriptomics shows great potential in providing this type of analysis to develop gut-modulating therapies as well as more personalized nutrition recommendations for bariatric surgery patients.